Analysis of The Influence of Company Fundamentals on Stcock Prices During the Transition Period and After the Implementation of the Remote Tranding System on the Stock Excange Indonesia (Study in Banking) - Taqiuddin, Ahmad; Isnurhadi, Isnurhadi; Yustini, Tien (CV. Era Digital Nusantara, 2024)
This study aims to determine the effect of ROE (Return on Equity, (PER) Price Earnings Ratio, DER (Debt to Equity Ratio), NPL (Non - Performing Loans), and BOPO (operating costs of operating income) on banking stock prices during the transition period and after the implementation of remote trading system technology on the Indonesian stock exchange and also examines whether there is a difference in the effect of these independent variables on stock prices in the two periods. This research was conducted with quantitative methods and used secondary data. The number of samples in this study was 6 banking companies listed on the Indonesia Stock Exchange from 2006 - 2020, where the transition period was from 2006-2009 and the remote trading period was from 2010-2020. The data were analyzed separately in both periods using multiple linear regression models, a classical assumption test, and also the Chow Test as an additional test using the SPSS 25 tool. The results showed that during the transition period only DER had no significant effect and 4 (four) other independent variables; BOPO, NPL, PER, and ROE have a significant effect on stock prices, while during remote trading the DER and PER variables have no significant effect and 3 (three) other independent variables; BOPO, PER, and NPL have a significant effect. During the transition period, the independent variables simultaneously have the effect of 70.3% on the price, but during the remote trading period, the ability of the five independent variables is only 35.5% in explaining the rise/fall of stock prices. The results of the Chow test show that there are differences in the influence or structural changes in the influence of independent variables on stock prices and the regression coefficients. There are also differences where the independent variables during the transition period are all inelastic (e < 1) and vice versa during remote trading all coefficient values the regression is elastic (e > 1).